Oral Health Assessment of Children with Autism Spectrum Disorder: Literature Review - Saerah Tul hikmah; Ratih Larasati; I Gusti Ayu Kusuma; Aini Binti Ahmad (International Journal of Advanced Health Science and Technology, 2022)
Children with autism have dental health problems that are often encountered, namely dental caries, periodontal disease, damage to the oral environment, tooth eruption disorders, and trauma. Coordination of irregular tongue movements causes food to often get stuck in the mouth and is not swallowed immediately, exacerbated by the habit of consuming cariogenic foods so that the risk of dental caries is higher in children with autism. This study aims to explain the oral health assessment in terms of oral hygiene in children with autism. The method used is a Systematic Literature Review obtained from four databases, namely Google Scholar, Pubmed, Wiley, and Science Direct. The results showed that the oral health assessment of children with autistic spectrum disorder was poor. There are still many autistic children who have caries and periodontal disease. It shows how difficult it is for autistic children and their parents to maintain healthy teeth and mouths. Factors that influence, among others, impaired concentration and interaction in children with autism is the lack of understanding of parents about maintaining dental and oral health. The benefit obtained from this literature review is to share insights that proper care by maintaining Dental oral and dental hygiene can improve tooth brushing skills in autistic children.